PMK 136/2024 and the Illusion of Progress: A Microdata-Based Assessment of Indonesia's Tax Gap - Putri, Andi Qur'ani Ratu Sabrina Arham (Riviera Publishing, 2025)
The analysis examines the effect of Minister of Finance Regulation Number 136 of 2024 (PMK 136/2024) on Indonesian tax ratio projections for 2025 until 2029. The regulation implements the Global Anti-Base Erosion (GloBE) Pillar 2 OECD/G20 rules. The simulation using microdata of 20 Indonesian multinational enterprises, tax ratio target and GDP growth from Perpres 12/2025. The study indicates a potential annual top-up tax revenue of approximately Rp43 billion. This potential tax revenue represents a negligible fraction of the estimated Rp44 trillion in tax losses until 2023. It highlighting the persistent issue of non-compliance and the limited standalone impact of PMK 136/2024 in addressing tax base erosion. The downward trend of top-up tax revenue projection to tax ratio demonstrates the improved corporate tax compliance among domestic tax obligations. From this study, researcher also finds the real main purpose of goverment by this regulation, which is to serve it as a tool to enhance compliance rather than a main state revenue source. The research confirms that effective tax enforcement combined with tax administration innovation is essential to achieving the 15% tax ratio target by 2029.